2020
DOI: 10.1002/smll.201907476
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phase Response as a Biological Mechanism‐of‐Action of (Nano)particle‐Induced Cardiovascular Disease

Abstract: Inhaled nanoparticles constitute a potential health hazard due to their size-dependent lung deposition and large surface to mass ratio. Exposure to high levels contributes to the risk of developing respiratory and cardiovascular diseases, as well as of lung cancer. Particle-induced acute phase response may be an important mechanism of action of particleinduced cardiovascular disease. Here, the authors review new important scientific evidence showing causal relationships between inhalation of particle and nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 107 publications
(163 reference statements)
2
69
0
Order By: Relevance
“…This could suggest that other particle components affecting the nanostructure in relation to the organic carbon content, in addition to SSA, are important contributors to the acute phase response of diesel exhaust particles. The acute phase response is an important cardiovascular disease risk factor [47], and inflammation may be linked to other pathologies including fibrosis [68] and secondary genotoxicity [69,70].…”
Section: Inflammation and Acute Phase Responsementioning
confidence: 99%
“…This could suggest that other particle components affecting the nanostructure in relation to the organic carbon content, in addition to SSA, are important contributors to the acute phase response of diesel exhaust particles. The acute phase response is an important cardiovascular disease risk factor [47], and inflammation may be linked to other pathologies including fibrosis [68] and secondary genotoxicity [69,70].…”
Section: Inflammation and Acute Phase Responsementioning
confidence: 99%
“…A review of occupational exposure to nanoparticles is beyond the scope here; however, we wish to mention a few examples of workplace exposure to noncombustion nanoparticles where health parameters have been measured (see also refs. [ 23,24 ] ). The examples below focus on inhalation exposure, and the reader is referred elsewhere for other routes of exposure such as oral [ 25,26 ] and dermal.…”
Section: Incidental Occupational Exposuresmentioning
confidence: 99%
“…[ 43 ] Similarly, volunteers that had been asked to spend several hours in settings with exposure to welding fumes exhibited a variety of inflammatory responses in the lung and blood. [ 24 ] Other occupational exposures of metal particles, such as steel plant or iron foundry workers, or occupations with exposure to particulates rich in aluminum or manganese, have shown indications of depressed anti‐inflammatory respiratory defences, and possibly even neurological symptoms. [ 24,44 ]…”
Section: Incidental Occupational Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Møller et al[23] reviewed the available literature on cell and animal studies, and concluded that the evidence of biodiesel-induced inflammatory, oxidative stress and genotoxicity response is weak and inconsistent between studies. Furthermore, engine type, combustion conditions and after-treatment have been identified as major determinants of the chemical composition of the diesel exhaust particles[47,81]. Thus, a major strength of the current study is that five different DEP were assessed in the same experimental setup, and that the three different fuel types were evaluated using the same engine, combustion conditions and after-treatment, thus ensuring comparability.…”
mentioning
confidence: 99%